Massive hemorrhagic pleural effusion - A rare presentation of acute pancreatitis (Indian Journal of Child Health, 2019)
Acute pancreatitis typically presents with a sudden-onset severe epigastric pain radiating to the back. Presentation with respiratory distress secondary to massive pleural effusion has been rarely reported. We report a 12-year-old girl presenting with complaints of fever, cough, dyspnea, and chest pain. Her chest radiograph showed massive pleural effusion and the pleural fluid amylase was markedly elevated. The patient recovered gradually with conservative medical management and the right side chest tube drainage. This report highlights the rare presentation of pancreatitis which requires a high index of suspicion for prompt diagnosis.